Asistensi Pembuatan Laporan Keuangan Berbasis Android bagi Usaha Mikro, Kecil, dan Menengah - Taufik Raharjo; Khusnaini Khusnaini (Universitas Serang Raya, 2018)
Micro, Small and Medium Enterprises (MSMEs) have shown their role in creating employment opportunities and as an important source for the growth of Gross Domestic Product. However, many MSME entrepreneurs do not understand yet the importance of financial planning and financial statements. So, they have not gained trust in accessing the capital facilities offered by the banks. The purpose of this community service activity is to raise the awareness of MSME entrepreneurs about the importance of business financial planning and the preparation of financial statements. The coaching of financial reporting skill is conducted using the